Personas y patrimonios: análisis del contenido de textos que abordan los vínculos identitarios - Olaia Fontal Merillas; Inmaculada Sánchez-Macías; Jesús Cepeda Ortega (Midas: Museus e Estudos Interdisciplinares)
In this research a content analysis is carried out concerning a participatory web page that keeps stories and photographs about people’s personal heritage (www.personasypatrimonios.com). As a fine perfume, heritage permeates the relationship of individuals and groups with tangible, intangible and spiritual elements. One only takes care of what is known; one value what one can understand and which makes us understand ourselves. Heritage at first smells suggests history or monument; but is not only that, lacking the spiritual elements of the perfume. In our study we claim an educational view, with its specific interests and keys connecting heritage assets with people.